Aplikasi Pupuk Kompos Kulit Buah Kakao terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopericum esculentum Mill.) - Siti Nur Hasanah; Elza Zuhry; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of cocoa pod compost and get the right dose to increase the growth and yield of tomato plants. The research was carried out starting from December 2016 to March 2017 conducted at the UPT Experimental Station, Faculty of Agriculture, University of Riau. The study was conducted experiments using a Completely Randomized Design (CRD) consisting of 6 treatments and 3 replications. The treatments are K0: Without doses of cocoa pod compost, K1: 10 tonnes.ha-1 (50 g/10 kg of soil), K2: 20 tonnes.ha-1 (100 g/10 kg of soil), K3: 30 tonnes.ha-1 (150 g/10 kg of land), K4: 40 tonnes.ha-1 (200 g/10 kg of land) and K5: 50 tonnes.ha-1 (250 g/10 kg of land). The parameters observed were plant height, age of flowering, stem diameter, age of harvest, number of fruits per plant, total weight of fruit per plant, total weight per fruit, fruit length, fruit diameter, number of fruit cavities and thick fruit flesh. The data obtained were analyzed using ANOVA and tested further with the Honestly Significant Difference test at the 5% point. The effects indicated that the application of cocoa pod composts significantly affected the parameters of plant height, age of flowering, stem diameter, age of harvest, number of plantations, total weight of fruit plantations, total weight per fruit, fruit length, fruit diameter and fruit flesh thickness. The total weight of fruit per plant has a positive correlation with plant height, stem diameter, number of fruit plants, thick fruit flesh, total weight per fruit, fruit length, fruit diameter, the number of fruit cavities. While the total weight fruit is negatively correlated with age at flowering and age at harvest. Cocoa pod compost dose 50 tonnes.ha-1 (250 g/10 kg soil) is the right dose for the growth and yield of tomato.Keywords: Tomato, Compost, Growth, Yield